Analisis Implementasi Patient Safety Terkait Peningkatan Mutu Pelayanan Kesehatan di Rumah Sakit - Sumarni Sumarni (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Ministry of Health of the Republic of Indonesia to set out five key issues related to safety in the hospital, the Patient Safety, worker safety, the safety of buildings and equipment in hospitals that could have an impact on Patient Safety and personnel, safety of the environment that have an impact on environmental pollution and safety businesses Hospital related to the survival Hospital. Management of patient safety plays an important role in improving the quality of health services. Patient safety is the efforts of service that prioritizes patient safety. The research was conducted at Ibn Sina Hospital, the type of research is cross sectional study is a draft that examines the dynamics of the correlation between the independent variables (patient safety) and the dependent variable (improving the quality of health services) at the same time. Respondents that all officers in the field of medical care and support services at Ibn Sina Hospital. The sampling technique used is random cluster sampling technique with a population of 402 respondents sampled 304 respondents. Based on interviews with the respondents stated that the higher the safety of the patient, the better the quality of a hospital, when a patient is exposed to the incident then it will switch to other hospitals, patient safety and quality are positively correlated Hospital. The results showed that no respondents (0%) the implementation of Patient Safety classified as very weak. The percentage of respondents to the implementation of Patient Safety is very strong, strong, moderate and weak amounted to 12.25% (30 respondents), 71.57% (224 respondents), 15.69% (39 respondents) and 0.49% (11 respondents ). Based on these results it is known that the majority of respondents ie 71.57% (224 respondents) is the implementation of the Patient Safety category are classified as strong, so it can be concluded that the implementation of Patient Safety at Ibn Sina Hospital relatively strong. Based on the dimensions of most of the dimensions Implementing Patient Safety at Ibn Sina Hospital is high with dimensions on the dimension of cooperation is highest in units amounted to 97.10%.